Phraséologie et didacticité dans les discours de vulgarisation médicale: une ergonomie discursive (PHRASIS | Rivista di studi fraseologici e paremiologici, 2021)
For several years many linguistic studies have been analysing prefabricated chunks in language, the “already-there”, “ready to talk” or “ready to write” (Plane and Rondelli, 2017 , Sitri and Tutin, 2016) – frozen sequences involving various linguistic levels : the lexicon, the syntax and the semantics. Our contribution proposes to re-examine a specific type of regularity: metalinguistic markers. These markers are polyfunctional. We will be interested in the work of negotiation which tries to give meaning to words through “discursive ergonomics”. In otherwords we are observing traces of didacticity that allow the reception of the other in the discourse.
Keywords: Scientific popularisation, didacticity, routines, prefabricated chunks, discursive ergonomics, cancer